The Gospel of Thomas and Plato A Study of the Impact of Platonism on the "Fifth Gospel" - Miroshnikov, Ivan (Nag Hammadi and Manichaean Studies, 2018)
In The Gospel of Thomas and Plato, Ivan Miroshnikov offers the first systematic discussion of the Platonist impact on the Gospel of Thomas, arguing that Platonism is indispensable to making sense of those sayings that have long remained exegetical cruces. Readership: All interested in the Nag Hammadi writings and the Gospel of Thomas, and anyone concerned with Middle Platonism and its impact on early Christian literature.